Avoiding under-reaching in twin circuit lines without residual current input from the parallel line - Mukerjee R.N.; Bin Abdullah M.F.; Tan K.K.; Nallagownden P. (2023)
Mutual coupling presents difficult problems during single phase to earth fault, in transmission line protection. In lines, on multiple circuit towers or on the same right of way, the zero-sequence circuits of the lines get mutually coupled, causing an error in the apparent impedance seen by the relay. This causes the distance protection relay at one end of the faulty line to overreach and the relay at the other end to under-reach. Also, incorrect sensing of the ground fault due to zero-sequence voltage inversion caused by mutual coupling in the zero-sequence network may lead to false trip of the neighbouring healthy line. The paper develops characteristic expressions for the effective sequence impedances experienced by a twin-circuit, both with and without mutual coupling and presents a non-iterative microprocessor based real time algorithm for computing fault distance and zero sequence compensation in basic distance relaying scheme, Residual current measurement from the parallel circuit is not required in the algorithm. 2007 RPS.